2009
DOI: 10.1134/s1063782609110098
|View full text |Cite
|
Sign up to set email alerts
|

Superconducting properties of silicon nanostructures

Abstract: Abstract. We present the findings of the superconductivity in the silicon nanostructures prepared by short time diffusion of boron after preliminary oxidation of the n-type Si (100) surface. These Si-based nanostructures represent the ptype high mobility silicon quantum well (Si-QW) confined by the δ -barriers heavily doped with boron. The ESR studies show that the δ -barriers appear to consist of the trigonal dipole centers, B + -B -, which are caused by the negative-U reconstruction of the shallow boron acce… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
21
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(29 citation statements)
references
References 63 publications
8
21
0
Order By: Relevance
“…The knee on the Δ(kT) dependence at T ≈ 146 K seems to be started from the change in the density of states involved into the recombination process. This temperature is in good agreement with the value of the critical temperature of the superconductor transition, T c ≈ 145 K, estimated from magnetic susceptibility, electrical resistivity and specific heat anomaly measurements [9]. So the charge correlations in the system of shallow boron acceptors seem to induce the observed distortion of parabolic densities of states at low temperatures revealed by spectral line-shape analysis.…”
supporting
confidence: 67%
See 1 more Smart Citation
“…The knee on the Δ(kT) dependence at T ≈ 146 K seems to be started from the change in the density of states involved into the recombination process. This temperature is in good agreement with the value of the critical temperature of the superconductor transition, T c ≈ 145 K, estimated from magnetic susceptibility, electrical resistivity and specific heat anomaly measurements [9]. So the charge correlations in the system of shallow boron acceptors seem to induce the observed distortion of parabolic densities of states at low temperatures revealed by spectral line-shape analysis.…”
supporting
confidence: 67%
“…Furthermore such high boron concentrations favor charge correlations starting to dominate in a system of shallow acceptors leading to their reconstruction into the trigonal dipole centers [3]. It appears to result in the high temperature superconductivity previously found in the silicon nanostructures with high concentration of boron [9]. The additional wide asymmetric spectral band detected at the lowest temperature (Fig.…”
mentioning
confidence: 85%
“…High-temperature superconductivity is typical of many other nanostructures. For example, it is typical of ultrathin NbC films and films from the aforementioned magnesium diboride, MgB 2 [168], ultra-narrow silicon (Si) quantum p-wells bounded by δ-barriers and heavily doped with boron [169], copper-containing fullerene quantum-well samples of endohedral nanostructures with the included element atom location inside the carbonic structure [170] and also of other nanostructures limiting the charge carrier movement in one, two, or three dimensions.…”
Section: Peculiar Properties Of Nanostructure Superconductivitymentioning
confidence: 99%
“…Similar behavior of the critical temperature and critical field for the superconducting transition have been observed during successive capture of vortices on large quantum dots "embedded" in bulk and low-dimensional structures based on classical and high-temperature superconductors. [28][29][30] These studies showed that the sequential capture of quantum vortices induces a quantization of the supercurrent in nanostructured superconductors which shows up in the corresponding oscillations of the critical temperature and critical field. [28][29][30][31] Given the dimensions of the microdefects in the plane of nanostructured CdB x F 2Àx d-barriers (d % 150 nm) 21,22 found by scanning tunneling microscopy (STM), the period of the oscillations in the critical temperature is in good agreement with the above model for quantization of the supercurrent.…”
Section: Introductionmentioning
confidence: 99%